2012
DOI: 10.2298/jsc121108148s
|View full text |Cite
|
Sign up to set email alerts
|

Controlled production of alginate nanocomposites with incorporated silver nanoparticles aimed for biomedical applications

Abstract: Production of nanocomposite alginate microbeads with electrochemically synthesized silver nanoparticles (AgNPs) based on electrostatic extrusion technique was investigated with respect to potentials for utilization in pharmaceutical and biomedical applications. It was shown that electrochemical synthesis of AgNPs results in reduction of practically all Ag+ ions present in the initial solution yielding stable Ag/alginate colloid solutions that were demonstrated to be suitable for sterilization, manipulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 2 publications
4
12
0
Order By: Relevance
“…This finding can be explained by alginate gel contraction during 48 h of gelling as reported previously. 26,40,41 It should be noted that the absorbance maximum increase and corresponding gel contraction were significantly higher in the case of HG alginate as compared to the LG alginate (~2.5-vs.~1.4-fold increase, respectively, Fig. 1).…”
Section: Production Of Ag/alginate Colloid Solutions and Discsmentioning
confidence: 88%
See 2 more Smart Citations
“…This finding can be explained by alginate gel contraction during 48 h of gelling as reported previously. 26,40,41 It should be noted that the absorbance maximum increase and corresponding gel contraction were significantly higher in the case of HG alginate as compared to the LG alginate (~2.5-vs.~1.4-fold increase, respectively, Fig. 1).…”
Section: Production Of Ag/alginate Colloid Solutions and Discsmentioning
confidence: 88%
“…In all experiments, dynamic uniaxial unconfined compression was performed in the regime 1 h on/1 h off, at the loading rate of 337.5 μm/s, 0.84 Hz frequency, and 0.2 mm total displacement corresponding to ~10% strain of the Ag/alginate disc. The compression parameters were selected based on cartilage tissue engineering studies reported in literature (e.g., ) and our previous studies of alginate based hydrogels …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[38][39][40] This method is particularly advantageous for potential applications in biomedicine and pharmacy due to the precise control of particle size and the use of only sodium alginate and silver precursors -AgNO 3 and KNO 3 , without chemical reducing agents because the silver ions are reduced to AgNPs by electrical current. Ag/alginate colloid solutions could be further crosslinked to form nanocomposite hydrogels in different forms such as films, sheets, microbeads 38,39,41 and microfibers. 42 In addition, the obtained nanocomposite hydrogels could be dried at room temperature with preservation of AgNPs.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, sodium alginate‐based silver nanocomposites have been reported for catalytic and antibacterial applications . NPs are incorporated into hydrogel matrix by simply mixing the NPs with the preformed hydrogel or by adding the NPs during the gelation process where the NPs could be entrapped during the swelling of the material.…”
Section: Introductionmentioning
confidence: 99%